Role of Mass Media in Achieving Accessible Healthcare - Shivani Kasturia; Divya (International Journal of Natural and Health Sciences, 2023)
The mass media's dissemination of health-related information, guidance, discoveries, and innovations to the general public is crucial to improving people's overall health. The dissemination and improvement of health-related information is one method that can be used to contribute to the goal of achieving accessible healthcare. Continuing and recurrent problems plague the healthcare industry. There are several issues to be concerned about, including the cost as well as the accessibility to high-quality medical care. The vast majority of patients are unaware of the most suitable medical facility to seek treatment for the myriad of conditions they suffer from. Enhancement of outcomes can be accomplished through disseminating information by the mass media to patients and promoting open and fruitful dialogue between patients and medical professionals